MoreMilk: Capacity building for safer milk and better nutrition - International Livestock Research Institute (International Livestock Research Institute, 2021)
The MoreMilk project is generating research evidence on how informal milk markets can be leveraged to improve nutrition and health, especially in peri-urban settings. The project's overall objective is to improve child health and nutrition outcomes through milk consumption.